PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH DI BMT UGT SIDOGIRI CAPEM PURWOHARJO KABUPATEN BANYUWANGI DALAM PERSEPEKTIF EKONOMI ISLAM - Ahmad Riswan; Norma Hadianto (Universitas KH. Mukhtar Syafaat, 2025)
The purpose of this study is: 1) To determine how the settlement of problematic murabahah financing is carried out at BMT UGT Sidogiri Purwoharjo Branch Office, and 2) To examine whether the settlement of problematic murabahah financing at BMT UGT Sidogiri Purwoharjo Branch Office is in accordance with the perspective of Islamic economics. This research employs a qualitative approach, and the data analysis technique used in this study is data reduction. The first step in handling problematic financing is contacting the member by telephone by the officer. The second step is conducting a field visit by the BMT to the member’s home to verify the situation as a preventive effort. The third step is issuing a Collection Report (Berita Acara Penagihan/BAP) when the previous efforts do not yield results; the BAP is carried out three consecutive times by the BMT. The fourth step is executing the collateral when all prior efforts fail to provide a solution. The settlement of problematic murabahah financing at BMT UGT Sidogiri Purwoharjo Branch Office is in accordance with the principles of Islamic economics and fulfills the pillars and conditions of murabahah. Likewise, the resolution process complies with generally applicable regulations.